2010
DOI: 10.4314/ajbr.v6i3.54045
|View full text |Cite
|
Sign up to set email alerts
|

Studies on effects of <i>Amaranthus spinosus</i> leaf extract on the haematology of growing pigs

Abstract: Ethanol extract of Amaranthus spinosus leaf (EEAL) was administered orally to growing pigs to determine its

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 0 publications
2
18
1
Order By: Relevance
“…According to Agati et al (2012) flavonoids can interfere in the mitotic process and therefore induce apoptosis depending on their nature and concentration. The ethanol extract of A. spinosus was reported to cause significant reduction in packed cell volume, RBC and Hb (Olufemi et al 2003). Saponins are subgroups of glycosides and are known to cause haemolysis of red blood cells (Lawrence et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Agati et al (2012) flavonoids can interfere in the mitotic process and therefore induce apoptosis depending on their nature and concentration. The ethanol extract of A. spinosus was reported to cause significant reduction in packed cell volume, RBC and Hb (Olufemi et al 2003). Saponins are subgroups of glycosides and are known to cause haemolysis of red blood cells (Lawrence et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Reports pertaining the effect of plant extracts on erythrocyte apoptosis are in their infancy. For instance, an altered RBC profile was observed after treatment with A. spinosus extract (Olufemi et al 2003). Furthermore, Saponin the major anti-nutritional compound present in most of the Amaranthus species was reported to induce 100% hemolysis at concentrations of 10 and 15 lg/ml (Arias et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Previous report of this plant showed that its extract was used as an antimalarial [6] , anti-diarrheic [7] , anti-diabetic, anti-hyperlipidemic and spermatogenic [8] , and anti-inflammatory activity [9] , stimulates proliferation of β-lymphocytes [10] and haematology. [11] Extract of this plant showed the presence of flavonoid. [12] The present study is focused to Pharmacognostical studies of A. spinosus.…”
Section: Introductionmentioning
confidence: 92%
“…A. spinosus is reported to possess antidepressant [13], anti-inflammatory [14], antimalarial [15], antiandrogenic [16], antihyperlipidemic, and spermatogenic activities [17]. Administration of A. spinosus extract restored the altered hematological parameters in pigs [18] and normalized biochemical changes in the epididymis of rats [19]. Amaranthine, isoamaranthine, hydroxycinnamates, rutin, quercetin, and kaempferol glycosides are some of the phytochemical constituents identified in A. spinosus .…”
Section: Introductionmentioning
confidence: 99%